A decentralized water/electricity cogeneration system integrating concentrated photovoltaic/thermal collectors and vacuum multi-effect membrane distillation. (1st September 2021) - Chen, Qian; Burhan, Muhammad; Akhtar, Faheem Hassan; Ybyraiymkul, Doskhan; Shahzad, Muhammad Wakil; Li, Yong; Ng, Kim Choon
Abstract: Cogeneration of electricity and freshwater by integrating photovoltaic/thermal collectors and desalination systems is one of the most promising methods to tackle the challenges of water and energy shortages in remote areas. This study investigates a decentralized water/electricity cogeneration system combining concentrated photovoltaic/thermal collectors and a vacuum multi-effect membrane distillation system. The merits of such a configuration include high compactness and improved thermodynamic efficiency. To evaluate the long-term production potential of the proposed system, a thermodynamic analysis is firstly conducted. Under the climatic conditions of Makkah, Saudi Arabia, the system can convert ∼70% of the solar irradiance into useful energy. The annual productivity of electricity and distilled water are 562 kWh and 5.25 m 3, respectively, per m 2 of the solar collector area. Electricity and water production rates are found to be impacted by hot water flowrate, feed seawater flowrate and heat storage tank dimension, while the overall exergy efficiency stabilizes at 25–27%. Based on the production rates, a life-cycle economic analysis is then conducted. The final desalination cost is calculated to be 0.7–4.3/m 3, depending on the solar collector cost and the electricity price. The derived results will enable a more in-depth understanding of the proposed solar-driven water/electricity cogeneration system. Highlights: A decentralized water/electricity cogeneration system driven by solar energy is evaluated. Nearly 70% of solar energy is converted into electricity/heat. Annual water and electricity output are 562 kWh and 5.25 m 3, respectively, per m 2 of collector area. Exergy efficiency is dominated by electricity generation and stabilized at 25–27%. Life-cycle cost of desalinated water is 0.7–4.3/m 3 .